Remote detection and maritime pollution chemical spill studies - Le Floch, Stephane; Muttin, Frédéric (ISTE, Ltd. ; Wiley, 2020)
The detection of marine pollution requires a scientific and operational response to identify contaminants, chemicals and hydrocarbons, and to support contrasting observations. Remote Detection and Maritime Pollution originates from the proceedings of CEDRE Information Day, held on October 13, 2016 in Brest, France. Containing four parts encompassing 13 chapters, this book explores remote detection channels for the multiform marine pollutions of today and of the future. With a focus on transatlantic cooperation, it covers remote detection sensors, the state of the art of maritime surveillance with regard to the interests of national and international authorities, the benefits of response strategy, and geophysical exploration. Future vectors (airplanes, drones, satellites, among others) and sensors (radar, optical, hyperspectral and so on) are also studied. This book is a valuable resource for practical solutions for marine authorities, industries (chemical, energy, aerospace, petroleum, shipping), lawyers and scientists.